Endovascular repair of ruptured abdominal aortic aneurysm - Šarac, Momir; Marjanović, Ivan; Tomić, Aleksandar; Šarac, Sanja; Bezmarević, Mihailo (Vojnosanitetski pregled, 2013)
Introduction. Rupture of an abdominal aortic aneurysm (AAA) is a potentially lethal state. Only half of patients with ruptured AAA reach the hospital alive. The alternative for open reconstruction of this condition is endovascular repair (EVAR). We presented a successful endovascular reapir of ruptured AAA in a patient with a number of comorbidities. Case report. A 60-year-old man was admitted to our institution due to diffuse abdominal pain with flatulence and belching. Initial abdominal ultrasonography showed an AAA that was confirmed on multislice computed tomography scan angiography which revealed a large retroperitoneal haematoma. Because of patient’s comorbidites (previous surgery of laryngeal carcinoma and one-third laryngeal stenosis, arterial hypertension and cardiomyopathy with left ventricle ejection fraction of 30%, stenosis of the right internal carotid artery of 80%) it was decided that endovascular repair of ruptured AAA in local anaesthesia and analgosedation would be treatment of choice. Endovascular grafting was achieved with aorto-bi-iliac bifurcated excluder endoprosthesis with complete exclusion of the aneurysmal sac, without further enlargment of haemathoma and no contrast leakage. The postoperative course of the patient was eventless, without complications. On recall examination 3 months after, the state of the patient was well. Conclusion. The alternative for open reconstruction of ruptured AAA in haemodynamically stable patients with suitable anatomy and comorbidities could be emergency EVAR in local anesthesia. This technique could provide greater chances for survival with lower intraoperative and postoperative morbidity and mortality, as shown in the presented patient.
Keywords: aortic aneurysm; abdominal; aortic rupture; comorbidity; diagnosis; vascular surgical procedures; blood vessel prosthesis; treatment outcome